Analisis Sifat Serat Tandan Kosong Kelapa Sawit Sebagai Material Akustik : Jurnal Review - Syabani, Nabilah A; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2025)
Oil palm empty fruit bunch (EFB) fiber is an agricultural waste that has potential as an environmentally friendly acoustic material. The high cellulose and hemicellulose content in TKKS plays a role in its ability to absorb sound, making it a more sustainable alternative to synthetic materials. This research aims to summarize and analyze studies related to the acoustic characteristics of TKKS, fiber processing, and the value of the sound absorption coefficient produced at various frequencies. The methods used in processing acoustic composites made from TKKS include mixing with polyester resin and hand lay-up techniques. The results of the analysis show that the TKKS composite material has good sound absorption capability at low to medium frequencies, with an absorption coefficient that meets the ISO 11654 standard. In addition, this study identified variables such as fiber length, composite thickness, and chemical treatment as important factors in optimizing the acoustic performance of TKKS. The results of this review are expected to provide insights for the utilization of TKKS as a sustainable acoustic material solution in the construction and soundproofing industries.